Analysis of Molecular Structure Changes in Humic Acids from Manure-Amended Soils over 17 Years Using Elemental Analysis and Solid-State 13C Nuclear Magnetic Resonance Spectroscopy - Ibrahim Mohammed; Busayo Kodaolu; Tiequan Zhang; Yutao Wang; Yuki Audette; James Longstaffe (Soil Systems, 2023)
Soil organic matter (SOM) plays an important role in regulating plant nutrient availability. Here, the effects of the long-term application of different forms of processed swine manure on the SOM structure are explored through the analysis of humic acid (HA) using elemental analysis and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy. The HAs from soils amended with liquid swine manure (LSM) and swine manure compost (SMC) are found to be more humified compared to the soils treated with solid swine manure (SSM) and the control (CK). The H/C and O/C molar ratios suggest that carboxyl-rich aliphatic structures are the most important class of biomolecules contributing to the LSM- and SMC-HA structures, while lignin-like structures are the most important biomolecules contributing to the CK- and SSM-HAs. SSM promoted the formation of aliphatic polar structures, which are more susceptible to aerobic biodegradation, whereas the CK facilitated the inclusion of condensed aromatic structures into the HA. Apart from the LSM-HA, the proportion of carboxylic acid functional groups reduced with manure application, while the proportion of phenolic acid functional groups increased. LSM-HA has the highest potential to enhance plant nutrient availability.